Neonatal purpura fulminans: A rare, life-threatening, and rapidly progressing disorder of coagulation - Rudrappa, Sudha; B, Thanuja; N S, Chandana (Indian Journal of Child Health, 2024)
Background: Neonatal purpura fulminans (NPF) is a life-threatening rare disease, which can be caused by deficiencies of protein C or protein S in a congenital or acquired manner. It is characterized by thrombosis of microvasculature, peri-vascular hemorrhage, and disseminated intravascular coagulation (DIC) occurring in the neonatal period. Clinical Description: A term female baby presented at 40 h of life with multiple purpuric rashes over the left foot which over 1 day extended until the knee. Over the next 3 days, there was rapid progression to involve extensive areas of necrosis with gangrene of toes of left foot, both forearms, bilateral temporal areas, peri-orbital regions, and left ear, in addition to multiple hemorrhagic blebs. Management and Outcome: Investigations showed anemia and thrombocytopenia with normal leucocyte count. DIC was suspected (INR 2), sepsis screen was negative, and fresh frozen plasma (FFP) was transfused 8th hourly. Arterial and venous Doppler was normal and blood culture showed no growth. Suspecting NPF, protein C, protein S, and anti-thrombin levels were sent, which showed a low protein C and protein S value. Mutations involving factor V Leiden, prothrombin gene, and MTHFR gene were not detected. The baby was started on low molecular weight heparin and, FFP and platelet concentrate replacement were continued, but she succumbed to the illness. Conclusion: NPF is a rare life-threatening entity that is fatal without prompt recognition of the condition. Therefore, it is necessary to recognize it early and initiate treatment.